SKOPOSTHEORIE IN POETRY TRANSLATION - Debora Wienda Rosari (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2011)
This article is conveying about translation and poetry as two inseparable yet never-ending phenomena. The translation of this especially written narrative is somehow tricky as a translator is usually required to satisfy the TL readers by providing a decent result. Poetry in TL is most of the time expected to come with equivalent dictions and form as written in SL. The writer here is trying to apply the notion of Skopostheorie in translating poetry. Based on the theory of skopos or ‘purpose’, one can choose to translate from SL to TL based on the purpose of the need. In the article, the writer gives the examples of two poems with different purpose of translating: One for the sake of the diction, while the other is for the sake of the form. At the level of conclusion, the Skopostheorie admits that not all ideals can be reached during the quest of poetry translation. Suggested by the Skopostheorie, a poetry translation has to have its own purpose and not to meddle it with others in order to produce a focused TL product.